2017
DOI: 10.1016/j.conb.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-remodeling enzymes in control of Schwann cell development, maintenance and plasticity

Abstract: Gene regulation is essential for cellular differentiation and plasticity. Schwann cells (SCs), the myelinating glia of the peripheral nervous system (PNS), develop from neural crest cells to mature myelinating SCs and can at early developmental stage differentiate into various cell types. After a PNS lesion, SCs can also convert into repair cells that guide and stimulate axonal regrowth, and remyelinate regenerated axons. What controls their development and versatile nature? Several recent studies highlight th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…This includes the Rac1–MKK7–JNK pathway and mTORC, which elevate c‐Jun and have been implicated as upstream activators of c‐Jun after nerve injury, and the cAMP pathway that suppresses c‐Jun (Arthur‐Farraj et al, ; Monje, Soto, Bacallao, & Wood, ; Norrmén et al, ; Shin et al, ). Histone deacetylase 2 (HDAC2), which is activated in injured nerves, also downregulates c‐Jun (Brügger et al, ; reviewed in Jacob, ). The transcription factors Krox20 and Oct6 also antagonize c‐Jun expression (Brügger et al, ; Parkinson et al, ).…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes the Rac1–MKK7–JNK pathway and mTORC, which elevate c‐Jun and have been implicated as upstream activators of c‐Jun after nerve injury, and the cAMP pathway that suppresses c‐Jun (Arthur‐Farraj et al, ; Monje, Soto, Bacallao, & Wood, ; Norrmén et al, ; Shin et al, ). Histone deacetylase 2 (HDAC2), which is activated in injured nerves, also downregulates c‐Jun (Brügger et al, ; reviewed in Jacob, ). The transcription factors Krox20 and Oct6 also antagonize c‐Jun expression (Brügger et al, ; Parkinson et al, ).…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
“…Several epigenetic processes regulate the repair Schwann cell phenotype (Ma & Svaren, ; reviewed in Jacob, ). Injury sets in train chromatin remodeling involving, first, the loss of the active histone mark H3K27 acetylation on enhancers of a number of myelin genes.…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…These have been catalogued in several recent reviews (Küspert & Wegner, ; Stolt & Wegner, ; Svaren & Meijer, ). Similarly, chromatin modifying activities and regulatory RNAs have been identified as important regulators in both types of myelinating glia (Gregath & Lu, ; Jacob, ; Svaren, ). In this review, we will concentrate on transcription factors and put the focus on the functional interactions within their networks.…”
Section: Introductionmentioning
confidence: 99%
“…It has become clear that epigenomic changes are important for such reprogramming events, employing mechanisms of gene activation and derepression (Brügger et al 2017; He et al 2018; Hung et al 2015; Jacob 2017; Ma and Svaren 2018). Our previous studies identified the association of trimethylation at Lys27 of histone H3 tail (H3K27me3) at promoters of many genes that become activated after peripheral nerve injury, and we found that the demethylation is required for full activation of some repair genes (Ma et al 2016).…”
Section: Introductionmentioning
confidence: 99%